What about the consumer choice? The influence of social sustainability on consumer's purchasing behavior in the Food Value Chain - Mariana Toussaint; Pablo Cabanelas; Tania E. González-Alvarado (European Research on Management and Business Economics (ERMBE), 2021)
The environmental, economic, and social impact of food value chains have attracted the attention ofa wide range of stakeholders. However, only a few studies have focused on sustainability in the foodindustry in terms of social responsibility from a developing country perspective. Indeed, existing analysishas not adequately addressed the role of social responsibility on consumers' preferences and purchasingdecision. This paper intends to shed light on this nexus through qualitative research relying on in-depthinterviews with decision-makers along the food value chain. Results suggest that consumers are sensitiveto social abuse practices, but they face difficulties to access information in order to inform their decisions.Therefore, a higher investment in transparency instead of certifications is recommendable, as sometimescompanies could be considered greenwashing. In this regard a number of opinion leaders, includingretailers and wholesalers, unions, media, and governments, can play a key role to enhance awarenessthrough information flows.
Keywords: M10; M14; M31; Q01; 650; Sustainability; Food value chain; Social responsibility; Consumers purchasing decisions